2007
DOI: 10.1128/aac.00692-07
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Metabolism and Persistence of the Anti-Human Immunodeficiency Virus Activity of 2′,3′-Didehydro-3′-Deoxy-4′-Ethynylthymidine, a Novel Thymidine Analog

Abstract: The therapeutic benefits of current antiretroviral therapy are limited by the evolution of drug-resistant virus and long-term toxicity. Novel antiretroviral compounds with activity against drug-resistant viruses are needed. 2,3-Didehydro-3-deoxy-4-ethynylthymidine (4-Ed4T), a novel thymidine analog, has potent anti-human immunodeficiency virus (HIV) activity, maintains considerable activity against multidrug-resistant HIV strains, and is less inhibitory to mitochondrial DNA synthesis in cell culture than its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 54 publications
1
33
0
Order By: Relevance
“…We also observed variability in the phosphorylation of different thymidine analogs (AZT and 4Ј-Ed4T) in some individuals. This may be due to the fact that the substrate specificity of the kinases at each phosphorylation step may be different or that more than one enzyme may be responsible for phosphorylation at each step (24,39). Turriziani et al also observed individual variability in TK-1 activity, though the variability was more marked in HIV-infected individuals than in healthy individuals (45).…”
Section: Downloaded Frommentioning
confidence: 91%
See 2 more Smart Citations
“…We also observed variability in the phosphorylation of different thymidine analogs (AZT and 4Ј-Ed4T) in some individuals. This may be due to the fact that the substrate specificity of the kinases at each phosphorylation step may be different or that more than one enzyme may be responsible for phosphorylation at each step (24,39). Turriziani et al also observed individual variability in TK-1 activity, though the variability was more marked in HIV-infected individuals than in healthy individuals (45).…”
Section: Downloaded Frommentioning
confidence: 91%
“…Five days postinfection, culture supernatant was harvested for HIV-1 RNA extraction using a QIAmp viral RNA extraction kit (Qiagen, Valencia, CA), according to the manufacturer's instructions. HIV-1 RNA extracted from culture supernatant was quantified using real-time RT-PCR with previously published primer set, probes, and cycling parameters (13 H]3TC for 24 h, and the intracellular metabolites were quantified using HPLC as previously described (39). In brief, after 24 h of incubation, the cells were harvested by centrifugation and washed twice in ice-cold phosphatebuffered saline (PBS) containing 20 M dipyridamole (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antiviral activity of 4Ј-Ed4T in cells persisted even 48 h after removal of the drug from culture, in contrast to the persistence of the antiviral activities of AZT and d4T (14). In this study, we found that no efflux of 4Ј-Ed4TMP and the less efficient efflux of 4Ј-Ed4T nucleoside from cells after drug removal might be one of the biochemical determinants for the longer retention of the 4Ј-Ed4T metabolites and the persistent antiviral activity of 4Ј-Ed4T in cell culture.…”
mentioning
confidence: 86%
“…Fusogenicity Assay-The fusogenicity assay was adapted from previously published studies (17)(18)(19)(20)(21). The day prior to the fusogenicity assay, 2 ϫ 10 4 TZMbl cells were plated in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%